Basında oligopolistik yapı ve tekelleşme - Paşalı, Nihal (My University, 1999)
THE OLIGOPOLISTIC STRUCTURE AND GETTING MONOPOLY IN MEDIA INDUSTRY SUMMARY In our country, almost all the basic or fundamental industries are completely controlled by giant oligopolistic corporations. An oligopoly exists when a few business firms dominate an industry. Oligopolies generally set prices as if they were monopolies. Large excess profits and inefficiency characterize their operations. The amount the oligopolist can sell at any price can be substantially affected by his rival's actions. Today, there are five groups in Turkey who has dominated 80% of the media industry. (Aydın Doğan, Dinç Bilgin, Cem Uzan, Enver Ören, Erol Aksoy) The most important cause of getting monopoly in media is being on the increase of the costs day by day. Nevertheless, the circulation of the newspaper and income of advertisement are fairly fallen in Turkey. In this manner, media firms are beginning the promotion activities but this factor is increasing cost much more. At the end of the oligopolistic structure in media, democracy is damaged. Getting monopoly is very dangerous in respect to freedom and democracy. However, media firms is increasing and being important in the world which would be global market. And getting monopoly in media will make media bosses new world boss. Nihal Paşalı İstanbul 1999 BASINDA OLİGOPOLİSTİK YAPI VE TEKELLEŞME

Ülkemizde hemen hemen tüm endüstrilerde tamamen dev oligopolistik yapıdaki kuruluşların kontrolüne rastlanmaktadır. Oligopol piyasaya hakim birkaç firmanın olması durumudur. Oligopolü oluşturan firmalar genellikle fiyat üzerinde neredeyse tekel gibi otorite sahibidirler. Onların hareketlerini bu kar maksimizasyonu ilkesi tanımlamaktadır. Oligopolde firmalar fiyatı oluştururken birbirlerinin kararlarından etkilenirler. Bugün Türkiye'de medya sektörünün %80'ini elinde bulunduran beş büyük medya holdingi bulunmaktadır. (Aydın Doğan, Dinç Bilgin, Cem Uzan, Enver Ören, Erol Aksoy) Medyada tekelleşmenin en önemli nedeni sektörde gün geçtikçe artan maliyetlerdir. Ayrıca Türkiye'de reklam gelirleri ve tiraj da son derece düşüktür. Bu nedenle basın işletmeleri promosyona yönelmiş fakat bu maliyetleri daha da artırmıştır. Medyadaki oligopolistik yapı demokrasinin zedelenmesine yol açar. Tekelleşme, özgürlük ve demokrasi açısından son derece tehlikelidir. Sonuç olarak, basın işletmeleri globalleşen dünyada giderek önem kazanmakta, medyada tekelleşme de medya patronlarını yeni dünyanın da patronu haline getirmektedir. Nihal Paşalı İstanbul 1999
Keywords: Basın; Gazetecilik; Genel Konular